Prosedur Penerbitan Certificate Of Pratique (COP) di Kantor Kesehatan Pelabuhan Belawan Oleh PT. Semesta Sejahtera Lestari Belawan - Ekin Lesmana Ginting; Dirhamsyah Dirhamsyah; Masringgit Marwiyah Nst (International Forum of Researchers and Lecturers, 2024)
The purpose of writing this paper is to find out the Procedure for Issuing a Certificate of Practice (COP) at the Belawan Port Health Office by PT. Semesta Sejahtera Lestari Belawan. The author collected data using two research methods, namely the field method (Field Research) and the library method (Library Research). The results of this research are the Procedure for Issuing a Certificate of Practice (COP) at the Belawan Port Health Office by PT. Semesta Sejahtera Lestari Belawan starts from submitting an application via the SINKARKES application (sinakarkes.kemkes.go.id). Then the agent logs in using the company account that has been registered in the SINKARKES application, after logging in the agent makes a request for the PNBP Certificate of Practice (COP) / Port Health Quarantine Certificate (PHQC) billing issuance service, then the company agent fills in the data and uploads ship documents such as: MDH (Maritime Health Declaration), SSCC/SSCEC, Medical Certificate/Drug Certificate (P3K), crew list, voyage memo, and last port clearance. After all data has been filled in completely and correctly, the agent can send the request by clicking create billing, the SINKARKES application will issue PNBP billing which must be permitted by PT. Semesta Sejahtera Lestari Belawan to carry out ship inspections together with the Port Health Quarantine.